PENINGKATAN PENGETAHUAN MAHASISWA MELALUI EDUKASI MENGHADAPI TANTANGAN DAN KESEMPATAN KARIER DI ERA SOCIETY 5.0 DI UNIVERSITAS ANDALAS - Sri Siswati; Syafrawati Syafrawati; Muthia Khairunnisa (LPPM (Institute for Research and Community Services) Universitas Andalas Padang, 2024)
The Society 5.0 era brings significant changes through technological innovations that transform work patterns and create new challenges in securing employment. Students are required to master both hard and soft skills to remain competitive in the workforce. A tracer study conducted by Andalas University revealed that nearly one-third of the 2023 graduates had not yet secured employment, raising concerns about their readiness to face this era. Therefore, the aim of this initiative was to enhance the preparedness of Andalas University students by increasing their knowledge of how to address challenges and career opportunities in the Society 5.0 era. The method used in this activity involved educational lectures and discussions conducted online via Zoom on May 31, 2024, attended by 103 students from Andalas University. The results showed an increase in students' knowledge of how to navigate the challenges and strategies for career opportunities in the Society 5.0 era, as measured by pre-test and post- test scores. Paired sample t-test analysis indicated a significant increase in the students' average knowledge, from 7.47 (pre-test) to 8.50 (post-test), with a p-value of 0.000 < 0.05. The conclusion of this activity is that the educational intervention effectively increased students' knowledge in facing challenges and career opportunities in the Society 5.0 era. It is hoped that Andalas University will continue to implement such programs, especially for final-year students, to better prepare them for the workforce and help reduce unemployment rates.